Correction of the homonymy of the nematode genus Singhiella Rao, 1958 (Oxyuridomorpha: Thelastomatoidea: Travasossinematidae) parasite from mole crickets (Insecta: Orthoptera: Gryllotalpidae) - Morffe, Jans; García, Nayla (Zootaxa, 2023)
N/A